2013
DOI: 10.5858/arpa.2012-0032-oa
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Phospho-mTOR Is Associated With Poor Prognosis in Patients With Gallbladder Adenocarcinoma

Abstract: Context.-Advanced gallbladder carcinoma (GBC) is a highly fatal disease with poor prognosis and few therapeutic alternatives. The mammalian target of rapamycin (mTOR) is a serine/threonine kinase that plays a central role in cell growth and homeostasis. Its regulation is frequently altered in various tumors and is an attractive target for cancer therapy; however, its status in GBC remains unclear.Objective.-To characterize immunohistochemical expression and prognostic significance of phospho-mTOR in advanced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…4A). As one of the primary kinases downstream of PI3K/Akt, mTOR has recently been reported to be substantially activated in GBC [18,19], which prompted our interest in exploring the potential activation of Akt-mTOR signaling cascades by FN. We first assessed the activation status of mTOR and its major downstream effectors (4E-BP1 and p70S6K) in FN-treated GBC-SD and NOZ cells.…”
Section: Fn Activates Akt/mtor/4e-bp1 Signaling Pathway In Gbcmentioning
confidence: 99%
See 1 more Smart Citation
“…4A). As one of the primary kinases downstream of PI3K/Akt, mTOR has recently been reported to be substantially activated in GBC [18,19], which prompted our interest in exploring the potential activation of Akt-mTOR signaling cascades by FN. We first assessed the activation status of mTOR and its major downstream effectors (4E-BP1 and p70S6K) in FN-treated GBC-SD and NOZ cells.…”
Section: Fn Activates Akt/mtor/4e-bp1 Signaling Pathway In Gbcmentioning
confidence: 99%
“…Recent studies have demonstrated that mTOR and p70S6K are substantially activated in GBC, especially in advanced tumors. Notably, highly expression of p-mTOR has been associated with worse prognosis in GBC patients [18,19]. Furthermore, the therapeutic targeting of mTOR was found to potently attenuate the migration and invasion of GBC cells via epithelial-mesenchymal transition inhibition [20].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of this protein in CG is an independent prognostic marker for CG progression (Sun et al 2011). Expression of connective tissue growth factor/CTGF in CG was correlated with better survival in two studies (Alvarez et al 2008;Garcia et al 2013), while in another investigation a role of CTGF expression in CG progression was found (Garcia et al 2013). Part of CGs produce several classes of mucins (see below).…”
Section: Other Factors Involved In Proliferation and Differentiation mentioning
confidence: 99%
“…The mammalian target of rapamycin (mTOR), a serine/threonine kinase, plays an essential role in the regulation of cell growth and is frequently deregulated in cancers. In CG, phospho-mTOR is an overexpression in early phases of cancer evolution, associated with poor prognosis (Leal et al 2013). The sphingosine-1-phosphate receptor 1 (S1P1) is overexpressed in CG, and higher levels of S1P1 were significantly correlated with tumor differentiation, tumor mass, lymph node metastasis, invasion, and decreased survival time ).…”
Section: Cell Cycle Regulationmentioning
confidence: 99%
“…Activation of the Akt/mTOR signaling pathway may also result from enhanced HER2, activation since a significant percentage of human GB tumors have been shown to have positive expression of HER2 and/or EGFR (23-26). Leal et al (27,28) reported that phospho-mTOR was associated with poor prognosis and the Akt/mTOR substrate P70S6K is frequently phosphorylated in patients with GBCa. Our results revealed that ~70% of BTC samples expressed mTOR, which did not deviate from the IGF-IR expression rate.…”
Section: A B C Dmentioning
confidence: 99%